COMPARATIVE ANALYSIS OF THE DISCLOSURE INDEX IN THE NOTES TO THE FINANCIAL STATEMENTS OF CENTRAL TAPANULI REGENCY FOR FISCAL YEARS 2023–2024 - Putri Adity, Safira; Soffi Sembiring, Adelya; Muda, Iskandar (JIAR : Journal Of International Accounting Research, 2025)
The title of this study is Comparative Analysis of the Disclosu re Index in the Notes to the Financial Statements of Central Tapanuli Regency for Fiscal Years 2023–2024. This study aims to analyze and compare the level of disclosure presented in the Notes to the Financial Statements (CaLK) of Central Tapanuli Regency for the fiscal years 2023 and 2024. The research applies a disclosure index method based on the Government Accounting Standards (SAP) as stipulated in Govern ment Regulation No. 71 of 2010. Each mandatory disclosure item was assessed using a binary scoring system, where a score of 1 was assigned if the item was disclosed and 0 if not. The index was then calculated to determine the overall level of compliance and transparency. The findin gs are expected to reveal whether there has been an improvement in the quality and completeness of disclosures over the two-year period. This study contributes to the literature on publ ic sector financial reporting by providing empirical evidence on the tran sparency and accountability of local government financial statements, with a specific focus on Centr al Tapanuli Regency. The results may also serve as input for local gove rnments in enhancing the quality of their financial reporting practices